Two-Day ABPM-Derived Indices and Mortality in Hemodialysis Patients. (12th October 2019) - Viazzi, Francesca; Cappadona, Francesca; Leoncini, Giovanna; Ratto, Elena; Gonnella, Annalisa; Bonino, Barbara; Verzola, Daniela; Garibotto, Giacomo; Pontremoli, Roberto
Abstract: BACKGROUND: Blood pressure (BP) and arterial stiffness are known cardiovascular risk factors in hemodialysis (HD) patients. This study examines the prognostic significance of 44-hour BP circadian rhythm and ambulatory arterial stiffness index (AASI) in this population. METHODS: A total of 80 HD patients underwent 44-hour ambulatory BP monitoring (ABPM) with a TM-2430 monitor during a standard midweek interdialytic interval and followed up for 4.5 ± 1.7 years. The end point was all-cause mortality. RESULTS: About 76% of participants were hypertensive (40% uncontrolled), 62% were nondippers, and 23% risers during the first interdialytic day, whereas 73% and 44% in the second day, respectively. During follow-up, 31 patients (40%) died. These showed higher pulse pressure (PP) and AASI44 and AASI of the second interdialytic period. The incidence of all-cause mortality was higher in HD patients with AASI44 > median, i.e. >0.54 (interquartile range = 14) (54% vs. 28%, χ 2 = 5.3, P = 0.021) when compared with those with lower AASI44 . Second, but not first-day ABPM-derived parameters, namely nondipping (log-rank χ 2 = 6.10, P = 0.0134) or reverse dipping status (log-rank χ 2 = 5.32, P = 0.210) and arterial stiffness index (log-rank χ 2 = 6.61, P = 0.0101) were significantly related to greater mortality. CONCLUSIONS: These findings indicate a strong relationship between arterial stiffness and cardiovascular risk and support a wider use of 44-hour ABPM recording for risk stratification in HD patients.